2017
DOI: 10.14687/jhs.v14i4.4832
|View full text |Cite
|
Sign up to set email alerts
|

Aggression levels of hearing impaired athletes: A comparison on individual and team sports<p>İşitme engelli sporcuların saldırganlık düzeyleri: Bireysel ve takım sporu üzerine bir karşılaştırma

Abstract: In hearing-impaired children, the opportunities for sportive activities from early chıldhood period are important for the development of physical and social skills. The purpose of this study was to determine the level of aggressiveness in hearing impaired athletes who perform individual and team sports. The sample of the research was consisted 109 hearingimpaired athletes participating in Hearing Impaired Basketball (n= 64) and Taekwondo (n=45) players Turkey Championship in 2016. A five-point Likert type Buss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The results match up with each other in terms of the sports branches selected are the individual sports. Işık et. al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results match up with each other in terms of the sports branches selected are the individual sports. Işık et. al.…”
Section: Discussionmentioning
confidence: 99%
“…As the age decreases, aggression levels of athletes increase. Işık et al (2017) found that as the ages of persons having impaired hearing, their aggression levels decrease. With reference to their comment, as the age increases, coping skills increase as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation